Food safety knowledge, attitude and practices of food handlers in food courts, Putrajaya, Malaysia - Abdullah, Mohd Firdaus Siau (2015)
The roles of food handlers were very important in preventing food contamination during its preparation and maintaining the cleanliness of food premises. Food handlers knowledge, attitude and practice in food safety is a key public health concern, because a large number of people take their meals outside the home and are potentially exposed to food borne illnesses. This cross sectional study aimed to explored the pattern of socio-demographic distribution, to assess the level of knowledge, attitude and practice of food safety; and the KAP relationship with the level of premise cleanliness in the food courts at Putrajaya. This study was conducted in two stages from May 2013 to July 2013. In the first stage, 274 food handlers were involved in this study via a self-administered questionnaire to assess their food safety knowledge, attitudes and practices. In the second stage, the cleanliness level of 64 food stall premises was determined through observation using recent inspection score done by the Health Authorized Officer from the Putrajaya Health Department. All completed questionnaires were validated manually and data analysis carried out by computer using SPSS version 20.0 software package. Distribution of food handlers socio-demographic profile was Malaysian (62.0%), male (70.4%), working experienced in food industry (82.0%) and attended food handler training (85.0%). The mean age was 28.7 years and 85.4% having income not less than RM 1,500 monthly. 78.5% of the food handlers had as primary/secondary school education. In respect to their participation in food sanitation trainings, 15.0% of all respondents had not attended any training. The findings reveal that food handlers’ knowledge, attitudes and practices were high with a mean percentage score more than 79.0%. However, the level of food safety practices (41.6%) among food handlers in Putrajaya needs to be improved to avoid negative views and to maintain the image of Putrajaya as Malaysia Administration Centre. The majority of the food courts in Putrajaya had consistently moderate level of cleanliness (63.5%) with the mean of 83.03%. Only 27.4% of the food courts were in the level of clean situation (>89% of premise cleanliness score) and 9.1% were not in the clean condition (<70% of premise cleanliness score). The findings of this study may help the health authorities in planning health intervention programs for food handlers to improve their KAP towards food safety and personal hygiene. Furthermore, this will in turn reduce the morbidity and mortality rate caused by food-borne diseases in the future.